2008
DOI: 10.1111/j.1447-0756.2008.00828.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of uterine cervical adenocarcinoma associated with small cell carcinoma

Abstract: Extrapulmonary small cell carcinomas are often associated with carcinomas of other cell types. Although a hypothesis that extrapulmonary small cell carcinomas arise from a multipotential stem cell could explain this mixed feature, recent molecular evidence supports another possibility that the small cell component may arise as a late-stage phenomenon in the progression of more organ-typical carcinomas. Here, we report a case of uterine cervical adenocarcinoma containing 30% of small cell carcinoma. Adenocarcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In the present study, 24% cases of SCCC presented with adenocarcinoma. This mixture phenomenon had been reported previously 18. Hence, the histological heterogeneity might indicate an origin from multipotent reserve cells.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the present study, 24% cases of SCCC presented with adenocarcinoma. This mixture phenomenon had been reported previously 18. Hence, the histological heterogeneity might indicate an origin from multipotent reserve cells.…”
Section: Discussionsupporting
confidence: 78%
“…Histologically, small-cell carcinoma was characterised by neuroendocrine-like architectural patterns, including nested and trabecular growth with common features 16. Some small-cell carcinoma cases included other types of carcinomas such as squamous-cell carcinoma or adenocarcinoma 17 18. In recent years, several studies reported that a non-small-cell-type high-grade neuroendocrine carcinoma of the gastrointerestinal tract was a distinct disease entity 19 20.…”
Section: Introductionmentioning
confidence: 99%